Levels of sirolimus in saliva and blood following mouthwash application. (24th March 2014) - Nudelman, Z; Friedman, M; Barasch, D; Nemirovski, A; Findler, M; Pikovsky, A; Gutkind, JS; Czerninski, R
<x xml:space="preserve">Abstract</x> Objectives Sirolimus (rapamycin) is a mammalian target of rapamycin (mTOR) inhibitor with antiproliferative activity. Its systemic administration is currently evaluated for the management of squamous cell carcinoma and various oral disorders. Topical oral application can enhance availability, efficacy and improve safety and compliance. Our objective was to evaluate the release profile and the safety of a sirolimus mouthwash. Subjects and methods A sirolimus mouthwash (0.05 mg ml−1) was applied to ten healthy male volunteers. Saliva and blood samples were taken after rinsing. Mass spectrometry and chemiluminescent microparticle immunoassay were used to determine saliva and blood levels of sirolimus. A topical oral release profile measurement and safety evaluation were performed. Results After rinsing with the mouthwash, a classic immediate release profile was noted in the oral cavity. Extremely high initial sirolimus levels rapidly declined over a 4‐hour period. Systemic exposure was limited, with a maximum level significantly lower than therapeutic doses, and safety was confirmed. Conclusions A single rinse with sirolimus mouthwash leads to high transient levels of the drug in the saliva. Although levels were variable, a therapeutic concentration was achieved topically along with minimal systemic absorption. These results broaden the potential clinical use of oral topical rapalogs.